2011
DOI: 10.1038/nchembio.560
|View full text |Cite
|
Sign up to set email alerts
|

Antitoxin MqsA helps mediate the bacterial general stress response

Abstract: SUMMARYAlthough it is well-recognized that bacteria respond to environmental stress via global networks, the mechanism by which stress is relayed to the interior of the cell is poorly understood. Here we show that enigmatic toxin/antitoxin systems play a vital role in mediating the environmental stress response. Specifically, the antitoxin MqsA represses rpoS, which encodes the master regulator of stress. Repression of rpoS by MqsA reduces the concentration of the internal messenger 3,5-cyclic diguanylic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
304
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(320 citation statements)
references
References 51 publications
14
304
1
1
Order By: Relevance
“…S7, suggest a common function of TA loci in persistence. On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…S7, suggest a common function of TA loci in persistence. On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 83%
“…The TA operons of E. coli that encode mRNases are induced by amino acid starvation via a Lon (Long Form Filament)-dependent mechanism (21,27,28). Direct evidence of Lon degradation of antitoxins has been obtained for RelB, MqsA, and YefM (27,29) (Fig. S2), whereas indirect evidence has been obtained in the cases of MazE, MazE-2 (ChpBI), HicB, YafN, and YgjM (HigA) (19,28).…”
mentioning
confidence: 93%
“…Second, more than 60 TA toxins are conserved between five members of the M. tuberculosis complex but not in 13 other closely related mycobacteria (9), raising the possibility that the large number of TA systems in M. tuberculosis is specifically important for TB pathogenesis. Third, TA systems have intriguing connections to stress responses and persistence, both in E. coli (1,2,11,12) and in M. tuberculosis (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Various TA loci in M. tuberculosis are induced during heat shock (23), hypoxia (9,21), DNA damage (20), nutrient starvation (13), macrophage infection (9,14,18), and antibiotic treatment (19,22), whereas other TA loci are down-regulated during macrophage infection (16) or salicylate treatment (15).…”
mentioning
confidence: 99%
“…It has been shown that, in many cases, the unfolded nature of the antitoxin protein or its unstructured C-terminal domain is the cause of its vulnerability to degradation by intracellular proteases. In most cases, the Lon protease, which represents a major class of ATP-dependent proteases, is involved in antitoxin degradation (2)(3)(4)(5)(6)(7)(8)(9)(10). There are also known TA systems that use the two-component protease ClpP, which cooperates with the ATPase-active chaperones ClpA or ClpX (11,12).…”
mentioning
confidence: 99%